Let's hear their voices : Cuban American writers of the second generation - López, Iraida H.; Rivero, Eliana S. (State University of New York Press, 2019)
"Let's Hear Their Voices brings together works by ten distinguished and emerging Cuban-American writers of the "second generation"--Writers who were born between 1960 and the mid-1980s in the United States to Cuban parents who either fled the island after 1959 or have a mixed ethnic background. Called "ABCs" (American-Born Cubans) or "AmeriCubans," these writers experiment with different formal approaches and lace their work with Cuban Spanish to give voice to hybrid identities and cultural legacies within the contemporary multicultural US. An introduction by Iraida H. López identifies key tropes in their poetry, prose, and drama and provides an overview of Cuban-American literature since the 1960s. With both original and previously published pieces by award-winning authors--including President Obama's Second Inaugural Poet, Richard Blanco--the volume makes a welcome contribution to the fields of Latinx and American literature, as well as critical discussions across disciplines about the intersections of latinidad with race, class, gender, and sexuality."-- Provided by publisher
Keywords: American literature -- Cuban American authors.; Cuban Americans -- Literary collections.; Cuba -- Literary collections.; Littérature américaine -- Auteurs américains d'origine cubaine.; Américains d'origine cubaine -- Anthologies.; Cuba -- Anthologies.; American.; Caribbean & Latin American.; LITERARY COLLECTIONS.; American literature -- Cuban American authors; Cuban Americans; Cuba; Electronic books.; Literary collections